Sistem Pendukung Keputusan Pemilihan Duta Bahasa Sumatera Utara Dengan Menggunakan Metode Promethee - Edwin Giovan Fanotona Zega (ADA Journal of Information System Research, 2024)
The process of selecting the North Sumatra Language Ambassador at the North Sumatra Language Hall is still classified as manual, there is no system that helps in the selection so that it takes a long time to process it, the accuracy of the selection process carried out is less precise and the resulting decision is less satisfying so that it makes it difficult for the jury to assess and make decisions to select the North Sumatra Language Ambassador at the North Sumatra Language Hall and the decisions made by the jury are less satisfying to the participants. Overcoming these problems, it is necessary to build a decision support system application for the selection of North Sumatra Language Ambassadors using the promethee method so that it helps and facilitates the jury in conducting assessments and making decisions to select North Sumatra Language Ambassadors and decisions that are determined by valid and satisfactory results. The final result decided that Hamsa Aulia Pohan with an outranking flow of 1.345833 was appointed as the North Sumatra Language Ambassador.